Gender Disparities affects Depression, Anxiety, Stress and Attentional performance among patients with Rheumatoid Arthritis - Chaurasia, Neha; Singh, Indramani Lal; Singh, Anup; Singh, Tara; Tiwari, Trayambak (International Journal of Psychosocial Rehabilitation, 2020)
There is a need to evaluate gender differences while referring to cognitive abilities. Among several psychological aspects, depression, anxiety, and stress emerge as significant psychological comorbidity. Rheumatoid arthritis (RA) is an acute, progressive, multifactorial condition that primarily affects physical as well as the mental functioning. Females are prone to have disease three times more than males. The present research was conducted to investigate gender disparities in depression, anxiety, and stress along with precise results on attentional performance in RA patients using a scale of anxiety, depression and stress, and Attentional Network Task (ANT). Twenty RA patients (ten male and ten female patients) were taken. The mean score of anxiety for female RA (X ̅= 12.00) was significantly higher than male RA patients (X ̅ =4.80) (t= 4.98, p<.001). The mean score of depression for female RA (X ̅ =10.70) was found significantly higher than male RA (X ̅=4.30) (t= 4.82, p<.001). Likewise, the mean score of stress for female RA patients (X ̅ =9.30) was also found significantly higher than male RA patients ((X) ̅ =5.60) (t= 2.75, p<.05). Results revealed that there was a significant gender difference in accuracy and executive control on ANT task performance. Overall, results indicated significant gender differences in anxiety, depression, stress, and attentional performance measures among RA patients. Results further suggested that women suffering from RA were significantly more affected by pain and its debilitating effects. This study would help rheumatologists for better understanding of treatment in patients to get recover rapidly from disease and improve their functional activity